Reconstructing Pollutant Dispersion Information by Defining Exhaust Source Parameters with Inverse Model - Arkadiy Dantsker; Patrick O’Brian (Proceedings, 2022)
The paper presents a solution of reconstructing the pollutant exhaust information that includes the rate of the exhaust and unknown parameters associated with pollutant dispersion required for the rate identification.